Palladium‐Catalyzed Silylcyanation of Ynamides: Regio‐ and Stereoselective Access to Tetrasubstituted 3‐Silyl‐2‐Aminoacrylonitriles. Issue 14 (2nd February 2022) - Hansjacob, Pierre; Leroux, Frédéric R.; Gandon, Vincent; Donnard, Morgan
Abstract: The palladium‐catalyzed silylcyanation of ynamides is described. This reaction is fully regioselective, delivering tetrasubstituted 2‐aminoacrylonitriles derivatives exclusively. Unexpectedly, the nature (aryl or alkyl) of the substituent located at the β‐position of the ynamide directly controls the stereoselectivity. The reaction tolerates a number of functional groups and can be considered as the first general access to fully substituted 2‐aminoacrylonitriles. Given the singular reactivity observed, a computational study was performed to shed light on the mechanism of this intriguing transformation. Relying on the specific reactivity of the newly installed vinylsilane functionality, the scope of 2‐aminoacrylonitriles has been enlarged by postfunctionalization. Abstract : Tetrasubstituted 2‐aminoacrylonitriles (α‐enaminonitriles) are underinvestigated building blocks due to the lack of methodologies to synthesize them in a controlled manner. A general access to these valuable scaffolds accompanied by mechanistic investigations and DFT calculations is described. This highly regio‐ and stereoselective strategy relies on the use of the first intermolecular silylcyanation of ynamides.